comparative evaluation of time domain and spectral domain optical coherence tomography in retinal nerve fiber layer thickness measurements - Angmo, Dewang; Bhartiya, Shibal; Mishra, Sanjay K; Sharma, Reetika; Poojari, Amar; Dada, Tanuj (Nepalese Journal of Ophthalmology, 2014)
Introduction: Before any new device can replace another for use in clinical practice, it is imperative that its reproducibility, diagnostic accuracy, and ability to detect changes over time are tested. Objective: To evaluate retinal nerve fiber layer (RNFL) measurements between two optical coherence tomography (OCT) systems: the Stratus OCT, a time domain system, and the Cirrus HD-OCT, a spectral domain system (both by Carl Zeiss Meditec, Inc., Dublin, CA). Materials and methods: An observational cross-sectional study was carried out involving 20 eyes with primary open angle glaucoma and 32 eyes of healthy controls. One eye of each patient was imaged on the same day with each instrument. The RNFL thicknesses measured by the two instruments were compared. Main outcome measures: Each clock hour, quadrant, and average RNFL thickness was determined on each of the two instruments. Statistics: The reliability was assessed by the intra-class correlation coefficient (ICC) and the Bland Altman plot for the limits of agreement for the overall mean RNFL thickness and for each quadrant. Results: A randomly selected eye of each of the 52 participants was analyzed. The mean temporal, superior, nasal and inferior RNFL thickness (in microns) were found to be 65.42 ±18.98, 114.85±26.67, 75.83±28.61 and 116.35±29.43 when measured by the Stratus OCT. In glaucoma patients these values were 55.06±18.22, 97.86±29.37, 63.44±24.89, and 102.94±38.20; and in controls these values were 70.59±17.40, 123.61±20.65, 82.03±28.67 and 123.06±21.63 respectively. The mean temporal, superior, nasal and inferior RNFL thickness (in microns) were 62.00±13.08, 112.00±25.13, 68.56±16.66 and 114.23±25.82 respectively, when measured with the Cirrus OCT. In glaucoma patients these values were 57.88±12.99, 98.56±26.88, 64.63±12.52 and 105.50±29.49; while in the control group these were 64.06±12.82, 118.72±21.63, 70.53±18.33, and 118.59±23.05 respectively. Intraclass correlation coefficient alpha (ICC alpha) for the temporal, superior, nasal and inferior quadrant RNFL thickness measurements were 0.81, 0.85, 0.66 and 0.93 respectively. Bland-Altman plots showed the limits of agreement (95%CI) for average RNFL to be 4.59 ±20.10 in the control group. In patients of glaucoma, Bland-Altman plots showed the limits of agreement (95%CI) for average RNFL to be 1.56±21.50. Conclusions: There is considerable variability in the RNFL thickness measurements made by the Cirrus and Stratus OCT that exceeds the limits of resolution afforded by the instruments. RNFL measurements obtained from the two OCT systems may not be used interchangeably. DOI: http://dx.doi.org/10.3126/nepjoph.v6i2.11692 Nepal J Ophthalmol 2014; 6(12): 185-191